MULTI-OBJECTIVE PATHFINDING FOR AUTONOMOUS ROBOT IN AGRICULTURE - Zangina, Umar; Buyamin, Salinda; Mahmud, Mohd Saiful Azimi; Aminu Yahaya Zimit; Zainal Abidin, Mohamad Shukri (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This paper enhanced the autonomy of an agricultural mobile robot in a structured environment to find an optimal path to perform selective and variable spray of pesticides. To realize these, a robust VRP scheme with variable deterministic demand and nonlinear travel time is designed to navigate the robot while making decisions to fulfill the pesticide demand at each node. Nonlinear time function obtained from experiments necessitates the consideration of three objectives simultaneously. The NSGA-III algorithm is adopted to determine the optimal path for the robot. To achieve this, the mixed integer algorithm is modified to handle the full integer complex routing problem to optimize three test case scenarios. Finally, the NSGA-III has shown the capability to solve the fully integer constraint problem based on the proposed modifications.